2020
DOI: 10.3390/polym12030554
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Assessment of Fibre Bridging Toughening Effects on the Compressive Behaviour of Delaminated Composite Plates

Abstract: Increasing the Mode I inter-laminar fracture toughness of composite laminates can contribute to slowing down delamination growth phenomena, which can be considered one of the most critical damage mechanisms in composite structures. Actually, the Mode I interlaminar fracture toughness (GIc) in fibre-reinforced composite materials has been found to considerably increase with the crack length when the fibre bridging phenomenon takes place. Hence, in this paper, the fibre bridging phenomenon has been considered as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…Compared with bolted connection, the new connection method can reduce stress concentration and fiber damage. Riccio [35] studied the effect of delamination on the compressive mechanical properties of composite laminate through experiments and simulations. Studies show that fiber bridging phenomenon is a natural toughening mechanism that can improve the interlayer strength of composite laminates.…”
Section: Research Backgroundmentioning
confidence: 99%
“…Compared with bolted connection, the new connection method can reduce stress concentration and fiber damage. Riccio [35] studied the effect of delamination on the compressive mechanical properties of composite laminate through experiments and simulations. Studies show that fiber bridging phenomenon is a natural toughening mechanism that can improve the interlayer strength of composite laminates.…”
Section: Research Backgroundmentioning
confidence: 99%
“…They concluded that it is possible to predict the Mode II interlaminar fracture toughness by using the formula where B is a coefficient that takes into account the additional shear stress contribution. Considering the loading conditions found in impact events, the main cause of failure within the composite structure can be related to the shear stress [ 41 , 42 , 43 ] localised within a structure during the dynamic loading. Consequently, it is possible to assume that Mode II failure is dominant and high dependency from the ply angle is expected for the G c value in this loading condition.…”
Section: Functionally Graded Pitch (Fgp) Laminatesmentioning
confidence: 99%
“…After being toughened, the resistance to the interlaminar crack growth is significantly improved; typically, the mode I (G IC ) and mode II (G IIC ) interlaminar fracture toughness of the composites will be greatly improved [18,19]. The increase in energy dissipation can be attributed to several mechanisms, such as the bridging caused by nanofillers and fibers, the increase in matrix viscoelasticity, and the deflection of the crack path [20,21].…”
Section: Introductionmentioning
confidence: 99%